Laparoscopy-assisted extended right hepatectomy for giant hemorrhagic hepatic cyst mimicking biliary cystadenocarcinoma: a case report - Yasunari Fukuda; Tadafumi Asaoka; Hidetoshi Eguchi; Keiichiro Honma; Eiichi Morii; Yoshifumi Iwagami; Hirofumi Akita; Takehiro Noda; Kunihito Gotoh; Shogo Kobayashi; Masaki Mori; Yuichiro Doki (Surgical Case Reports)
Abstract Background Hemorrhagic hepatic cysts infrequently involve several iconographic changes requiring a differential diagnosis, primarily with a cystic malignancy. We herein report a case of laparoscopy-assisted extended right hepatectomy for a giant hemorrhagic hepatic cyst with an enhancing mural nodule that was clinically suspected of being biliary cystadenocarcinoma. Case presentation A 73-year-old woman was followed up for giant hepatic cyst occupying the right lobe of the liver. During the follow-up, an enhancing mural nodule was newly noted on computed tomography in 2016. Based on additional clinical examinations, biliary cystadenocarcinoma was undeniable, and laparoscopy-assisted extended right hepatectomy was performed for diagnostic and therapeutic purposes. She had no perioperative complications and was discharged on postoperative day 13. A histological examination of the mural nodule showed neovascularization within an organized hematoma. Conclusion We herein report a rare case of giant hemorrhagic hepatic cyst mimicking biliary cystadenocarcinoma that was successfully treated with laparoscopy-assisted extended right hepatectomy. Laparoscopic surgery in our case was an effective procedure performed with the utmost care.